Evaluation of White Weathered Mushrooms for Reduction of Lignin and Improvement of Animal Feed Digestion from Coconut Coir Waste - Siti Sabariyah; Muhammad Jufri; Sayani Sayani; Rahman Dani Lasamadi (Jurnal Penelitian Pendidikan IPA, 2026)
Limited forage availability due to land conversion has become a major constraint in goat farming development. Therefore, the utilization of agricultural waste as alternative feed is increasingly important, including young coconut husk waste which is abundant but underutilized. However, its high lignocellulosic content, particularly lignin, limits digestibility and nutritional value for ruminants. This study aimed to evaluate the ability of several white-rot fungi to reduce lignin content and improve the cellulose characteristics of young coconut husk waste as a potential alternative feed ingredient. The research was conducted in two stages: fungal selection and optimization of fermentation conditions. The first stage used five fungal treatments, namely Trichoderma sp. TR3, Pleurotus sajor-caju, Pleurotus ostreatus, Trametes versicolor, and Lentinus edodes. Parameters observed included lignin and cellulose contents after 20 days of incubation. The second stage evaluated the effect of incubation period (20, 30, and 40 days) and inoculum volume (0.5, 0.7, and 1.0 mL) using Pleurotus sajor-caju as the selected fungus. The results showed that Pleurotus sajor-caju produced the lowest lignin content (17.93%) and the highest cellulose content (48.80%) compared with other fungi. In the optimization stage, the lowest lignin content was observed in treatment A3B1 (40 days incubation and 0.5 mL inoculum) at 15.47%, while the highest cellulose content was obtained in treatment A2B1 (30 days incubation and 0.5 mL inoculum) at 61.15%. These findings indicate that Pleurotus sajor-caju has strong potential for selective delignification of young coconut husk waste while maintaining cellulose content. Biological fermentation using white-rot fungi can therefore be considered a promising and environmentally friendly approach for improving the quality of lignocellulosic waste as ruminant feed